A case on Thai students in EFL program in Indonesia (learning problems and strategies) - Samalee, Hakimee (Institut Agama Islam Negeri IAIN Salatiga, 2017)
This research aims to investigate Thai students in EFL (English as Foreign Language) Program in Indonesia, focusing on the learning problems and strategies of nine Thai female students who study in English Department of IAIN Salatiga. This study uses descriptive qualitative design. The descriptive data analysis is employed to describe the research findings which are primarily mined from the transcriptions of in-depth interview. The results show that all Thai students have various problems during their study in Indonesia. The complication emerges when they must learn foreign languages and use them to learn at the same time. They must learn language skills (listening, reading, writing, speaking) on one hand and use those skills for practical or functional purposes on the other hand. It seems like one is not yet finished but they have to simultaneously practice it for functional purposes of communicating with the lecturers, understanding the tasks given, etc. We indicated that most strategies used by 6 participants were asking friends instead of teachers. Further, we also found distinct strategies personally preferred by the participants to learn EFL in their convenience.